Development of Mathematics Student Worksheets Through the Approach Model Eliciting Activities (MEAs) on the Triangle Material. Issue 1 (June 2021) - Munir, N P; Anas, A; Sunarti,; Mursalin, N R; Natsir, I
Abstract: Student Worksheet is one of the teaching materials needed by teachers on the mathematics learning process to achieve basic competencies needed. The objective of this study is protype final, quality, and effectiveness of the development of worksheets based on the MEAs approach of triangel material. This type of R & D (Research and Development) research adopts the ADDIE development model. The trial sujects in this study are Grade VII students of SMP Negeri 1 Suli, Luwu Regency. Tehnique collection data that used were validity data obtained from validation sheets by experts, practicality data obtained from student response questionnaires and effectiveness data obtained from student learning outcomes tests. The data obtained were analyzed using descriptive statistics. The results of this study indicate that: The final prototype of the worksheet product developed had suitable with the principles of the MEAs approach, ther are: identifying problems, simplifying problems, building mathematical models, transforming and solving models, and interpreting the results; the quality of worksheet for validation is 85% in the very valid category, the average practicality is 73% in the practical category; and the effectiveness of the student worksheet score average 87% is in the very effective category increasing student learning outcomes in the material triangle.